PENINGKATAN PRODUKTIVITAS KACANG TANAH MELALUI PENGEMBANGAN MESIN PENGUPASNYA - Hasan Zuhdi; Nani Mulyaningsih (Wahana Ilmuwan, 2016)
Along with the development of technology, it is necessary to create the means or equipment if it can improve the effectiveness of the work, one of them in agriculture. There is now a peanut peeler machine, but the condition is considered not to work optimally. This is because the current engine speed is considered too slow, so it has not been able to peel the nut as a whole, only 50% of the peanut peeling entered in the stripper house. For that, the authors intend to develop technologies peanut peeler machine so that productivity can be increased.The method used in this research by analyzing the effect of the spin machine to the result and the stripping time. Variations in engine speed is used ranging from 52 rpm, 68 rpm and 84 rpm. Of the various rounds of the engine, will get round that is ideal for achieving peanut peeler machine work optimally in a short time.The results showed that the peanut peeler machine can work optimally with the result of 35.6 kg /hour at 84 rpm rotation speed of the engine, so that number can later be used as a reference for the agricultural industry to increase its production.